Light microclimate-driven changes at transcriptional level in photosynthetic grape berry tissues - Garrido, Andreia (2021)
Viticulture practices that change the light distribution in the grapevine canopy can interfere with several physiological mechanisms, such as grape berry photosynthesis and other metabolic pathways, and consequently impact the berry biochemical composition, which is key to the final wine quality. We previously showed that the photosynthetic activity of exocarp and seed tissues from a white cultivar (Alvarinho) was in fact responsive to the light microclimate in the canopy (low and high light, LL and HL, respectively), and that these different light microclimates also led to distinct metabolite profiles, suggesting a berry tissue-specific interlink between photosynthesis and metabolism. In the present work, we analyzed the transcript levels of key genes in exocarps and seed integuments of berries from the same cultivar collected from HL and LL microclimates at three developmental stages, using real-time qPCR. In exocarp, the expression levels of genes involved in carbohydrate metabolism (VvSuSy1), phenylpropanoid (VvPAL1), stilbenoid (VvSTS1), and flavan-3-ol synthesis (VvDFR, VvLAR2, and VvANR) were highest at the green stage. In seeds, the expression of several genes associated with both phenylpropanoid (VvCHS1 and VvCHS3) and flavan-3-ol synthesis (VvDFR and VvLAR2) showed a peak at the véraison stage, whereas that of RuBisCO was maintained up to the mature stage. Overall, the HL microclimate, compared to that of LL, resulted in a higher expression of genes encoding elements associated with both photosynthesis (VvChlSyn and VvRuBisCO), carbohydrate metabolism (VvSPS1), and photoprotection (carotenoid pathways genes) in both tissues. HL also induced the expression of the VvFLS1 gene, which was translated into a higher activity of the FLS enzyme producing flavonol-type flavonoids, whereas the expression of several other flavonoid pathway genes (e.g., VvCHS3, VvSTS1, VvDFR, and VvLDOX) was reduced, suggesting a specific role of flavonols in photoprotection of berries growing in the HL microclimate. This work suggests a possible link at the transcriptional level between berry photosynthesis and pathways of primary and secondary metabolism, and provides relevant information for improving the management of the light microenvironment at canopy level of the grapes.